Leading Against the Clock: Lived Experiences of School Heads in Navigating Leadership and Time Demands in Public Elementary Schools - REYNALDO TUBIJE (International Journal of Education, Literacies and Curriculum Studies, 2026)
School heads operate at the intersection of instructional leadership, administrative accountability, personnel management, stakeholder engagement, and school improvement, making time one of their most constrained leadership resources. This qualitative phenomenological study explores the lived experiences of public elementary school heads in navigating leadership responsibilities and competing time demands in Benito Soliven North District, Schools Division of Isabela, Philippines. Specifically, it seeks to understand the situations that intensify time pressure, the meanings school heads attach to these experiences, the strategies they employ to negotiate competing priorities, and the insights they develop from leading under persistent temporal constraints. Participants are purposively selected school heads with direct and sustained experience in managing public elementary schools. Data are generated through semi-structured, in-depth interviews and analyzed using thematic analysis informed by phenomenological principles. The inquiry is sensitized by the Philippine Professional Standards for School Heads while allowing meanings and themes to emerge inductively from participants' narratives. Particular attention is given to tensions among administrative compliance, instructional leadership, personnel concerns, stakeholder expectations, unexpected school demands, and personal boundaries. The study is expected to illuminate time not merely as a scheduling concern but as a leadership resource negotiated through prioritization, delegation, relational coordination, adaptability, and professional judgment. Findings may inform leadership-development initiatives, administrative workload policies, and context-responsive support mechanisms intended to protect school heads' capacity for instructional and strategic leadership.